2005
DOI: 10.1112/s0010437x05001314
|View full text |Cite
|
Sign up to set email alerts
|

The 2-adic eigencurve at the boundary of weight space

Abstract: We prove that, near the boundary of weight space, the 2-adic eigencurve of tame level 1 can be written as an infinite disjoint union of 'evenly spaced' annuli, and on each annulus the slopes of the corresponding overconvergent eigenforms tend to zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
116
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(121 citation statements)
references
References 5 publications
4
116
1
Order By: Relevance
“…In Buzzard-Calegari [3], the following theorem is proved, using similar techniques to those in [16], [11] and [4]: Theorem 6. The slopes of the U 2 operator acting on 2-adic overconvergent modular forms of weight 0 are…”
Section: Previous Work and New Directionsmentioning
confidence: 98%
See 2 more Smart Citations
“…In Buzzard-Calegari [3], the following theorem is proved, using similar techniques to those in [16], [11] and [4]: Theorem 6. The slopes of the U 2 operator acting on 2-adic overconvergent modular forms of weight 0 are…”
Section: Previous Work and New Directionsmentioning
confidence: 98%
“…It also uses methods developed by Smithline in his thesis [16] and applied by him in [17], which were then also used in the author's paper [11] and in the paper of the author with Buzzard [4].…”
Section: Previous Work and New Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained will be independent of r, since it is known that any overconvergent U -eigenform of finite slope must extend to a function on X 0 (1) ≥p −r for all r < p p+1 (see [Buz03]). The slopes of U are somewhat mysterious; the complete list of slopes is known only for p = 2, tame level 1 and weight 0 by [BC05], and for 2-adic, 3-adic and 5-adic weights near the boundary of weight space by [BK05], [Jac03] and [Kil06] respectively. There are conjectures ( [Buz05], [Cla05]) for a general weight, prime and level, but these appear to be rather inaccessible at present.…”
Section: Computations Of Slopesmentioning
confidence: 99%
“…Progress is being made, however. Recent work of Buzzard and Kilford [BK05] shows us that the 2-adic eigencurve indeed looks quite simple at the boundary of the weight space (3) : it is the disjoint union of infinitely many p-adic annuli. Using this, Buzzard and Calegari [BC] have shown that the 2-adic eigencurve is proper over the weight space.…”
Section: Generalisationsmentioning
confidence: 99%